Pharmacogenetics biomarkers of antipsychotics’ safety in adolescents with acute psychotic episode - D. V. Ivashchenko; N. I. Buromskaya; P. V. Shimanov; D. V. Deitch.; K. A. Ryzhykova; Е. A. Grishina; Yu. S. Shevchenko; D. A. Sychev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Currently, there is a lack of pharmacogenetic research of antipsychotics’ safety in children and adolescents with acute psychotic episodes. Genetic polymorphisms of CYP2D6 and ABCB1 are the most likely candidates for such studies. AIM.To establish possible associations of CYP3A, CYP2D6, ABCB1 polymorphisms with safety of antipsychotics of an acute psychotic episode in adolescents during the first 14 days of treatment. MATERIALS AND METHODS. We observed 53 adolescents, hospitalized with acute psychotic episode, during 14 days of treatment. Mean age was 15,08±1,7 years. All patients took antipsychotic as the main drug. The tolerance to antipsychotics was assessed using UKU SERS, SAS, BARS. We collected a buccal epitelium from each patient and genotyped CYP3A4*22 (rs2740574), CYP3A5*3 (6986A>G, rs7767746), CYP2D6*4, *10 (rs3892097, rs1065852), ABCB1 1236C>T (rs1128503), 2677G>T/A (rs2032582), 3435C>T (rs1045642) by real-time PCR. RESULTS. Scores of UKU SERS, SAS, BARS, AIMS scales did not correlated with average doses of antipsychotics. Distribution of genetic polymorphisms were in the Hardy-Weinberg equilibrium. The carriage of CYP2D6*4 was associated with the presence of «Asthenia / Lassitude / lncreased Fatigability» (70% vs. 3.6%, p=0.039), the carriage of CYP2D6*10 was associated with «Increased dream activity» (53.8% vs. 22.5%, p=0.043). The «Increased Duration of Sleep» was more often observed in homozygotes according to the polymorphisms ABCB1 2677G>T/A (50% vs. 15.8%, p=0.006) and 3435C>T (41.7% vs. 8.2%, p=0.007). Carriers of TT polymorphism homozygote ABCB1 2677G>T/A also more frequently noted «Polyuria/polydypsia» (37.5% vs. 5.18%, p=0.045). CONCLUSION.Genetic polymorphisms CYP2D6*4, *10, ABCB1 2677G>T/A and 3435C>T increased a risk of adverse drug effects of antipsychotics in adolescents with acute psychotic episode.